2023
DOI: 10.3389/fpsyg.2023.1146944
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal amplitude of low-frequency fluctuation values as a neuroimaging biomarker for major depressive disorder with suicidal attempts in adolescents: A resting-state fMRI and support vector machine analysis

Abstract: ObjectiveMajor depressive disorder (MDD) is associated with suicidal attempts (SAs) among adolescents, with suicide being the most common cause of mortality in this age group. This study explored the predictive utility of support vector machine (SVM)-based analyses of amplitude of low-frequency fluctuation (ALFF) results as a neuroimaging biomarker for aiding the diagnosis of MDD with SA in adolescents.MethodsResting-state functional magnetic resonance imaging (rs-fMRI) analyses of 71 first-episode, drug-naive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…MDD patients with suicide attempts showed an increase of ReHo values in the cingulum gyrus, and these changes were associated with the level of suicide attempts (Yang et al, 2022). In addition, MDD patients with a history of suicide attempts exhibited abnormal brain activation in the medial superior frontal gyrus and precuneus, which might be helpful for identifying at‐risk individuals (Zhou et al, 2023). The precuneus is considered as the core hub of DMN, which plays a crucial role in a diverse array of highly integrated functions including self‐referential processing, episodic memory retrieval and emotion regulation (Cunningham et al, 2017; Utevsky et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…MDD patients with suicide attempts showed an increase of ReHo values in the cingulum gyrus, and these changes were associated with the level of suicide attempts (Yang et al, 2022). In addition, MDD patients with a history of suicide attempts exhibited abnormal brain activation in the medial superior frontal gyrus and precuneus, which might be helpful for identifying at‐risk individuals (Zhou et al, 2023). The precuneus is considered as the core hub of DMN, which plays a crucial role in a diverse array of highly integrated functions including self‐referential processing, episodic memory retrieval and emotion regulation (Cunningham et al, 2017; Utevsky et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…FC is not a suitable candidate for meta-analysis unless all studies are the same kind of network study[ 7 ]. To our knowledge, although many previous studies have used ReHo, ALFF, and fALFF methods and rs-fMRI to explore the changes in spontaneous brain activity in adolescent depression patients[ 8 - 17 ], the results of these studies are inconsistent and are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported abnormal ALFF values in various brain regions of depressed adolescents with suicide attempts compared to healthy controls or depressed adolescents without suicide attempts. These regions include the medial superior frontal gyrus (mSFG), the precuneus, the middle and inferior frontal gyri, the middle and superior temporal gyri, the occipital cortex, the anterior cingulate cortex (ACC), the medial prefrontal cortex (mPFC), the hippocampus, and the thalamus (7,8). The abnormal ALFF values in these regions may reflect impaired functions such as emotion regulation, self-referential processing, cognitive control, memory, and salience detection (9).…”
Section: Introductionmentioning
confidence: 99%